Molecular taxonomic reassessment of the Cloud Forest’s Bolitoglossa salamanders (Caudata: Plethodontidae) from Cordillera de Mérida (Mérida state, Venezuela) - Fermin, Gustavo; García-Gutiérrez, Javier; Escalona, Moisés; Mora, Andrés; Díaz, Amelia (Zootaxa, 2012)
Salamanders found at different localities nearby Mérida city, Venezuela, are thus far reported as Bolitoglossa orestes or B.spongai. However, morphological ambiguities among individuals from several populations of both putative species, besidestheir reported disparate geographical distributions, prompted us to clarify the specific identity of these bolitoglossines throughthe sequence analysis of their corresponding 16S rRNA genes. Seventeen specimens belonging to the vertebrates collection ofUniversidad de Los Andes (CVULA), collected at separated cloud forests in Sierra La Culata (San Eusebio, Macho Capaz andSan Javier del Valle) and Sierra Nevada de Mérida (La Mucuy), were used to extract DNA upon tissue digestion. Sequenceanalysis of the 16S rRNA gene supports a biogeographical scenario where, so far, there is only one salamander species for eachsierra: B. orestes, which is widely distributed in Sierra La Culata, and a so far undescribed species of a Venezuelan bolitogloss-ine apparently restricted to Sierra Nevada de Mérida. Based on our molecular results and an examination of morphological evidence, B. spongai should be considered a synonym of B. orestes.